Effect of natural and artificial feeding on growth and survival African catfish seeds (Clarias gariepinus) - Prastya, Gygih Rudi Eka; Mumpuni, Fia Sri; Wahyudin, Yudi (Universitas Djuanda, 2024)
Feed is an essential element that supports cultured fish's growth and survival. The purpose of the study was to determine the effect of differences in natural and artificial feeding on the growth and survival of dumbo catfish fry (Clarias gariepinus). The research was conducted from July to August 2022 with an experimental period of 40 days. The study used a completely randomized design with three treatments (artificial feeding, maggot feeding, and blood worm feeding) with four replications. The data analysis used was an analysis of variance (ANOVA), which was further tested using the least real difference (BNT). Test parameters include specific weight growth rate, specific length growth rate, absolute length, absolute weight, survival rate, and feed efficiency. The results showed that blood worm feeding significantly affected the parameters of specific weight growth rate, specific length growth rate, absolute length, and absolute weight (P < 0.05). The best growth was found in the bloodworm feeding treatment (specific weight growth rate 4.67 ± 0.31%/day, LPPS 1.88 ± 0.12%/day, absolute length 6.50 ± 0.49 cm, absolute weight 10.26 ± 1.29 g). Artificial and natural feed treatments did not significantly affect survival rate and feed efficiency.